2019
DOI: 10.1177/1937586719861553
|View full text |Cite
|
Sign up to set email alerts
|

Using Interdisciplinary Dress Rehearsal Events to Ensure Staff Readiness When Opening a New Healthcare Facility

Abstract: Objective: This nonresearch article describes best practices of using the simulation-based Dress Rehearsal method to prepare staff to move into a new hospital or a new space in an existing facility and to ensure the new facility is ready for use. The authors introduce a modified version of the interactive sociotechnical analysis (ISTA) model to serve as the academic foundation for the Dress Rehearsal concept. Background: Healthcare organizations that build new medical facilities must ensure the space is ready … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…In addition to this, developing necessary digital skills, navigating and becoming familiar with new technology was perceived by nurses as time‐consuming and increasing their workload. This finding is consistent with other studies, which showed that implementing new technology in healthcare demands more time of staff (Arguilera, Dickey, & Guzman, 2020; Knippa & Senecal, 2017) and nurses have also reported that the use of technology can be time‐consuming making them time‐poor (Chang et al., 2016; Dowding et al., 2015; Holtz & Krein, 2011; Staggers et al., 2018). These increase demands faced by nurses during the implementation phase of integrating technology needs to be met with additional resources (i.e.…”
Section: Discussionsupporting
confidence: 90%
“…In addition to this, developing necessary digital skills, navigating and becoming familiar with new technology was perceived by nurses as time‐consuming and increasing their workload. This finding is consistent with other studies, which showed that implementing new technology in healthcare demands more time of staff (Arguilera, Dickey, & Guzman, 2020; Knippa & Senecal, 2017) and nurses have also reported that the use of technology can be time‐consuming making them time‐poor (Chang et al., 2016; Dowding et al., 2015; Holtz & Krein, 2011; Staggers et al., 2018). These increase demands faced by nurses during the implementation phase of integrating technology needs to be met with additional resources (i.e.…”
Section: Discussionsupporting
confidence: 90%
“…Yellow Brick has facilitated Dress Rehearsal events throughout North America in healthcare facilities of all sizes and services, including critical access hospitals, clinics, ambulatory and outpatient facilities, community hospitals, specialty hospitals such as children's hospitals and behavioral health facilities, and large, academic medical centers. We have conducted lessons-learned sessions and developed best practices that we have shared at national conferences, through webinars, on our blog, and in the article, Using Interdisciplinary Dress Rehearsal Events to Ensure Staff Readiness When Opening a New Healthcare Facility (Aguilera, Dickey, & Guzman, 2019). We continue to lead the industry to establish best practices that we share with our clients and the healthcare community.…”
Section: Our Journeymentioning
confidence: 99%